Carbonitriding of ZrO2: relation between the weight loss and crystalline phase evolution during reaction - Tamborenea, Silvina Alejandra (2005)
Carbonitriding reactions of ZrO2 permit to obtain Zr(C,O,N) phases that belong to the pseudoternary “ZrO–ZrN–ZrC” system. The Zr(C,O,N) phase has cubic crystalline structure with a0 parameter depending on the C, O and N content. The formation reaction of the Zr(C,O,N) phases was followed using X-ray diffraction (XRD) and the weight loss (WL) data. The reaction was studied employing different carbon contents (15–31%) at temperatures from 1400 to 1650 ◦C. The -phase (Zr7O9.5N3.0) was the unique secondary product formed. The crystallite sizes of the zirconium phases were also determined by XRD. Some samples were analyzed using the Rietveld method with silicon as internal standard. Using the carbonitriding process a Zr(C,O,N) phase was obtained and the loss weight is a parameter permitting to control the reaction products. The oxidation resistance of the Zr(C,O,N) phase was studied employing differential thermal analysis (DTA)–thermogravimetric analysis (TG) techniques. Additionally, microstructure analysis of raw materials and reaction products were performed by scanning electronic microscopy (SEM). The reaction was studied employing different carbon contents (15¨C31%) at temperatures from 1400 to 1650 ¡ãC. The ¦Â¡å-phase (Zr7O9.5N3.0) was the unique secondary product formed. The crystallite sizes of the zirconium phases were also determined by XRD. Some samples were analyzed using the Rietveld method with silicon as internal standard. Using the carbonitriding process a Zr(C,O,N) phase was obtained and the loss weight is a parameter permitting to control the reaction products. The oxidation resistance of the Zr(C,O,N) phase was studied employing differential thermal analysis (DTA)¨Cthermogravimetric analysis (TG) techniques. Additionally, microstructure analysis of raw materials and reaction products were performed by scanning electronic microscopy (SEM).